Introducing Summer Mungbean in cereal based production system - Venkatesh, M. S.; Hazra, K. K.; Singh, Jagdish; Nadarajan, N. (Indian Farming, 2015)
Increasing the land productivity with highly intensive cropping system is the need of the day to meet the growing demand of food grain. Rice-wheat and maize-wheat systems contributing the major share in food grain production are now facing the problem of decline in factor productivity with reduction in farm income. Introducing summer mungbean after harvesting of wheat is a potential option for increasing system productivity and long-term sustainability in these cereal based production system.